2015
DOI: 10.1007/s10509-015-2597-8
|View full text |Cite
|
Sign up to set email alerts
|

From horseshoe to quasi-satellite and back again: the curious dynamics of Earth co-orbital asteroid 2015 SO2

Abstract: Earth co-orbitals of the horseshoe type are interesting objects to study for practical reasons. They are relatively easy to access from our planet and that makes them attractive targets for sample return missions. Here, we show that near-Earth asteroid (NEA) 2015 SO 2 is a transient co-orbital to the Earth that experiences a rather peculiar orbital evolution characterised by recurrent, alternating horseshoe and quasisatellite episodes. It is currently following a horseshoe trajectory, the ninth asteroid known … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A very interesting case of mean motion resonance are the co-orbitals, that is, objects with the same orbital period or trapped in the resonance 1:1. There are several examples of co-orbitals in the solar system, and quasi-satellites are probably the most interesting [22]. They seem to be satellites of a planet but are just revolving around the Sun with the exact same planetary orbital period, sometimes ahead of the planet and sometimes behind, generating a relative trajectory with respect to the planet that seems to be a satellite-like orbit.…”
Section: Orbital Resonancesmentioning
confidence: 99%
“…A very interesting case of mean motion resonance are the co-orbitals, that is, objects with the same orbital period or trapped in the resonance 1:1. There are several examples of co-orbitals in the solar system, and quasi-satellites are probably the most interesting [22]. They seem to be satellites of a planet but are just revolving around the Sun with the exact same planetary orbital period, sometimes ahead of the planet and sometimes behind, generating a relative trajectory with respect to the planet that seems to be a satellite-like orbit.…”
Section: Orbital Resonancesmentioning
confidence: 99%
“…Spectroscopic analysis has shown that some members of this cluster exhibit a distinctive olivine-dominated composition that lends further support to the common origin scenario (Borisov et al 2017). On the E-mail: nbplanet@ucm.es other hand, most known Mars Trojans are believed to be primordial objects that may have remained in their current dynamical state since Mars was formed (Christou 2013;de la Fuente Marcos & de la Fuente Marcos 2013a;Christou et al 2017). The stability of Mars Trojans in general and of relevant known objects in particular has been studied by e.g.…”
Section: Introductionmentioning
confidence: 99%